Genetic characterisation of the Theileria annulata cytochrome b locus and its impact on buparvaquone resistance in bovine. (December 2022) - Ali, Qasim; Zahid, Osama; Mhadhbi, Moez; Jones, Ben; Darghouth, Mohamed Aziz; Raynes, George; Afshan, Kiran; Birtles, Richard; Sargison, Neil D.; Betson, Martha; Chaudhry, Umer
Abstract: Control of tropical theileriosis, caused by the apicomplexan Theileria annulata, depends on the use of a single drug, buparvaquone, the efficacy of which is compromised by the emergence of resistance. The present study was undertaken to improve understanding of the role of mutations conferring buparvaquone resistance in T. annulata, and the effects of selection pressures on their emergence and spread. First, we investigated genetic characteristics of the cytochrome b locus associated with buparvaquone resistance in 10 susceptible and 7 resistant T. annulata isolates. The 129G (GGC) mutation was found in the Q01 binding pocket and 253S (TCT) and 262S (TCA) mutations were identified within the Q02 binding pocket. Next, we examined field isolates and identified cytochrome b mutations 129G (GGC), 253S (TCT) and 262S (TCA) in 21/75 buffalo-derived and 19/119 cattle-derived T. annulata isolates, providing evidence of positive selection pressure. Both hard and soft selective sweeps were identified, with striking differences between isolates. For example, 19 buffalo-derived and 7 cattle-derived isolates contained 129G (GGC) and 253S (TCT) resistance haplotypes at a high frequency, implying the emergence of resistance by a single mutation. Two buffalo-derived and 12 cattle-derived isolates contained equally high frequencies of 129G (GGC), 253S (TCT), 129G (GGC)/253S (TCT) and 262S (TCA) resistance haplotypes, implying the emergence of resistance by pre-existing or recurrent mutations. Phylogenetic analysis further revealed that 9 and 21 unique haplotypes in buffalo and cattle-derived isolates were present in a single lineage, suggesting a single origin. We propose that animal migration between farms is an important factor in the spread of buparvaquone resistance in endemic regions of Pakistan. The overall outcomes will be useful in understanding how drug resistance emerges and spreads, and this information will help design strategies to optimise the use and lifespan of the single most drug use to control tropical theileriosis. Graphical abstract: Image 1 Highlights: First link between genetic mutations and buparvaquone drug resistance in T. annulata. The data will help to design strategies to optimise the use and lifespan of the single most drug use to control tropical theileriosis.